An Experimental and Quantum (QTAIM) Performance Study of a Proposed Molecular Chemosensor: A Quinazolinone‐Based Sensor for Hg2+ Ion Detection. Issue 9 (28th February 2023) - Hadi, Hamid; Safari, Reza; Landarani‐Isfahani, Amir; Shamlouei, Hamid Reza
Abstract: This work synthesized a novel colorimetric ligand based on the compound quinazolinone (Sensor) and investigated it. The sensing activity of the sensor toward different cation was studied. The sensor demonstrated a highly selective colorimetric sensing toward Hg 2+ with a detection limit of 0.1 ppb and visual color change from colorless to Purple in methanol‐water solvents (v/v, 10, 90). The cation binding character was determined using visual inspection, UV–Vis, and fluorescence analyses. In the computational part, the interaction between the receptor and Hg 2+ ion was investigated using density functional theory (TD‐DFT) and quantum theory of atoms in molecules (QTAIM) in the solution phase (in the presence of water as solvent and the CPCM model). Theoretical studies have shown that electronic properties such as energy gap, absorption energy, charge/energy transfer, and optical properties change dramatically in the presence of Hg 2+ cations. Also, the effect of the electric field on the electronic properties of the sensor/Hg 2+ complex improved the Hg 2+ cation adsorption process. Abstract : In this work, we focused our research on the selective detection of mercury (Due to high toxicity), which helps to prevent various harmful diseases caused by mercury pollution. The results of this research showed that this chemosensor synthesized has the potential and ability to selectively detect Hg2+ cation (limit of detection (LOD)) up to 0.1 ppb (0.1 μg/molar).